Is there an incremental rise in the risk of obstetric intervention with increasing maternal age. - Gunasekara, M.D (My University, 2004)
Objective of this prospective obstruction study to detect increasing maternal age increases the risk of operative delivery and to investigate such a relationship is due to maternal age itself or due to medical and obstetric complications. Six hundred and fifty one nulliparous women with singleton cephalic pregnancies delivering at term (37-42 weeks of gestation)were included. They were categorized into four groups (age 20-24 years, age 25- 29 years, age 30-34 years, age 35 years and above).Basic social and obstetric data were obtained by a structured questionnaire and ward records. The data were subjected to logistic regression to obtain an odds ratio and 95 percentage confidence interval for each intervention. Rates of elective caesarean section, induction of labour, spontaneous vaginal delivery, instrumental vaginal delivery, emergency caesarean section and also rates of medical and obstetric complications. There was a positive, highly significant association between increasing maternal age and obstetric intervention. Elective (p 0.001) and emergency( p0.00l) caesarean section, instrumental vagin delivery(p 0.001) and induction of labour (p 0.001) all increased with increasing a. e. In the second stage of labour lack of progress requiring emergency caesarean section was more likely with increasing maternal age although it is not significant statistically( p 0.001). Incremental increase in emergency caesarean section can not be explained by the increasing medical and obstetric complications alone. This study demonstrates that increasing maternal age is associated with an incremental increase in obstetric intervention that can not be explained by the medical and obstetric complications alone. Previous studies have demonstrated a significant effect in women older than 35 years of age but these data show changes on a continuum from 20 years of age. This finding may reflect a progressive, age related deterioration in myometrial function